Lucy Holborn, The Long Shadow of Apartheid: Race in South Africa since 1994: Somewhat lacking in conceptual and methodological imagination (Historia, 2021)
The Long Shadow of Apartheid presents information on events and issues concerning race relations in South Africa. It contains sets of summaries of newspaper reports, comments on the reported events and "racial sentiments" reflected in the reports; transcripts of interviews with public notables; and renditions of selected results from opinion surveys. My focus is on part one, Race in the Press. This comprises "a review of expressions of racial sentiment by decision-makers (very loosely defined) and reports on inter-group tensions as reflected in the print media" (pp 1-2).